Efeitos do treinamento f??sico com v??deo game ativo e do treinamento combinado com exerc??cio resistido em crian??as e adolescentes asm??ticos: ensaio clinico controlado, aleatorizado e cego - Mello, Maryj??se Carvalho (2017)
Asthma is a chronic inflammatory disease of the airways, such as children and adolescents. In this sense, active video games (VGA) and resistance exercise have been gaining prominence as a form of training in this age group, promoting adhesion, motivation, reduction of pulmonary inflammation, muscular strength gain and energy expenditure. Thus, the objective of this study was to evaluate whether the increase of aerobic (combined) exercise reduces a pulmonary inflammation and improves clinical control in children and adolescents as trainers more effectively than only aerobic training with VGA. This is a randomized, blinded clinical trial with no registry Clinical Trials.gov: NCT03014154, 30 children and adolescents were randomly assigned to a VGA group using XBOX 360 Kinect Adventure "Reflex Ridge" (VGA group) and unladen exercises and VGA group associated with resistance exercise (VGAR group) with intensity 3 sets of 15 repetitions, with 50% of 1 RM. The training period lasted 8 weeks and involved 2 weekly sessions of 1 hour and 10 minutes, 10 minutes. heating, 30 min. of VGA, 20 min. of exercises and 10 min. the elongation. Pulmonary inflammation, pulmonary function, peak flow, respiratory muscle strength, as anthropometric variables, clinical control questionnaires and quality of life, physical fitness and peripheral muscular strength of the participants before and after the training were evaluated. The results, involving 27 study participants (13 VGA and 14 VGAR) showed reduction in lung inflammation in both groups (clinically important) but the effect size (TE) for reduction of FeNO in the VGA group was 0 , 47 (small) and in the VGAR group was 0.68 (mean). In TCP it occurred in the test week, velocity, slope and distance traveled only in the VGA group. And in the VGAR group, improvement in physical fitness and rapid cardiovascular return to basal condition by HR recovery after the test (TE = 0.90) was higher in relation to the VGA group (TE = 0.41). Maximum load increase after 1RM test (MMSS from 2 kg to 4 kg (TE = 1,28) and MMII from 30 kg to 51 kg (TE = 1,09)) was also higher in the VGAR group. In both groups, there was improvement in quality of life and better clinical control of the disease, and no participants in both groups were not in exercise-induced bronchospasm during the sessions. These results allowed us to conclude that combined training is more effective in reducing pulmonary inflammation and allows an improvement in quality of life, clinical control of the disease, aerobic fitness, physical fitness and muscular strength in children and adolescents.